2020
DOI: 10.3389/fmicb.2020.554784
|View full text |Cite
|
Sign up to set email alerts
|

Multilocus Sequence Types and Antimicrobial Resistance of Campylobacter jejuni and C. coli Isolates of Human Patients From Beijing, China, 2017–2018

Abstract: Campylobacter species are zoonotic pathogens and the leading cause of bacterial enteritis worldwide. With the increase of antimicrobial resistance to fluoroquinolones and macrolides, they have been identified by the World Health Organization (WHO) as high-priority antimicrobial-resistant pathogens. There is currently little known about the prevalence and antimicrobial resistance characteristics of Campylobacter species in Beijing. In this study, we performed a 2-year surveillance of Campylobacter in Beijing, C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
29
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 55 publications
(69 reference statements)
6
29
1
Order By: Relevance
“…The majority of C. jejuni strains were assigned to CC21; this finding supports previous observations which shows CC21 is the most prevalent CC worldwide [33]. Within CC21, ST-50 was the dominant ST in our clinical samples, although not all of previous studies reported ST-50 as the dominant sequence type [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of C. jejuni strains were assigned to CC21; this finding supports previous observations which shows CC21 is the most prevalent CC worldwide [33]. Within CC21, ST-50 was the dominant ST in our clinical samples, although not all of previous studies reported ST-50 as the dominant sequence type [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…The majority of C. jejuni strains were assigned to CC21; this nding supports previous observations which shows CC21 is the most prevalent CC worldwide [33]. Within CC21, ST-50 was the dominant ST in our clinical samples, although not all of previous studies reported ST-50 as the dominant sequence type [34,35].…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies in Korea [14,22,54] and other countries [55][56][57][58][59] have reported diverse STs in C. coli isolated from food animals and humans, and ST827, ST828, ST829, and ST855 were the predominant STs. The most frequent STs identified in this study (ST854, ST1016, ST2715, ST829, ST860, and ST9867) differed from those described in previous reports [55][56][57][58][59], except for ST829 C. coli, which was frequently detected in pigs in Korea [22]. Genetic diversity in the Campylobacter population might emerge through mutation and recombination events [59].…”
Section: Discussionmentioning
confidence: 88%
“…Indeed, 8 of the STs (ST860, ST828, ST829, ST854, ST1016, ST1096, ST1556, and ST2715) were identified in both chicken and pigs. Previous studies in Korea [ 14 , 22 , 54 ] and other countries [ 55 , 56 , 57 , 58 , 59 ] have reported diverse STs in C . coli isolated from food animals and humans, and ST827, ST828, ST829, and ST855 were the predominant STs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation